Semiotic analysis of zero waste campaigns on instagram - Senia Afifah; Kinkin Yuliaty Subarsa Putri (Journal of Education, Social & Communication Studies, 2026)
This study examines the symbolic construction of environmental messages in a zero waste campaign post published by Zero Waste Indonesia on Instagram dated March 12, 2026. The objective of this research is to analyze how meaning is produced and communicated through visual and textual elements in social media-based environmental campaigns. This study employs a qualitative research approach using semiotic analysis based on Roland Barthes’ framework, focusing on three levels of meaning: denotation, connotation, and myth.The findings reveal that the analyzed content operates as a complex system of signs that constructs environmental meaning beyond its literal representation. At the denotative level, the post depicts the reality of waste accumulation and its management. At the connotative level, the content frames waste as a serious and potentially hazardous issue while highlighting the social dimension of environmental problems. At the level of myth, the message constructs an ideological narrative emphasizing collective responsibility, positioning audiences as both contributors to environmental degradation and agents of change. Furthermore, the study demonstrates that social media functions as a powerful platform for environmental communication by integrating visual storytelling and persuasive messaging. The findings suggest that zero waste campaign content not only informs but also influences audience perceptions, moral awareness, and attitudes toward sustainable behaviour.